Alternating and direct current characterization and photoinduced absorption studies of modified conjugated polymer thin films - BLAU, WERNER; COLEMAN, JONATHAN; DRURY, ANNA (My University, 2004)
Control of interchain separation enables the optical properties of polymer thin films to be altered. We present a thin film preparation technique that increases the free volume fraction in spin coated polymer thin films resulting in reduced interchain interaction. The polaron yield, measured using photoinduced absorption, was significantly reduced as a direct result of the increased interchain separation, leading to a higher value for the measured photoluminescence efficiency. Impedance spectroscopy showed an increase in permittivity, probably due to greater polarizability. Increases approaching one order of magnitude were observed for direct current hole conductivity and mobility values. Space charge limited conduction analysis suggests a narrowing of the highest occupied molecular orbital band tail on treatment resulting in reduced trapping. Single layer light emitting devices prepared using this technique were found to be significantly brighter and to have longer operating lifetimes
PUBLISHED
Keywords: Physics; Control of interchain separation